Descriptive epidemiology of selected birth defects, areas of Lombardy, Italy, 1999 - Frassoldi Emanuela; Gambino Maria; Pisani Salvatore; Bellotti Maria; Vergani Daniele; Tittarelli Andrea; Maghini Anna; Fabiano Sabrina; Caramaschi Fausta; Tessandori Roberto; Tagliabue Giovanna; Costa Enrica; et al. (BMC, 2007)
Abstract Background Birth defects are a leading cause of neonatal and infant mortality in Italy, however little is known of the etiology of most defects. Improvements in diagnosis have revealed increasing numbers of clinically insignificant defects, while improvements in treatment have increased the survival of those with more serious and complex defects. For etiological studies, prevention, and management, it is important to have population-based monitoring which provides reliable data on the prevalence at birth of such defects. Methods We recently initiated population-based birth defect monitoring in the Provinces of Mantova, Sondrio and Varese of the Region of Lombardy, northern Italy, and report data for the first year of operation (1999). The registry uses all-electronic source files (hospital discharge files, death certificates, regional health files, and pathology reports) and a proven case-generation methodology, which is described. The data were checked manually by consulting clinical records in hospitals. Completeness was checked against birth certificates by capture-recapture. Data on cases were coded according to the four-digit malformation codes of the International Classification of Diseases, Ninth Revision (ICD-9). We present data only on selected defects. Results We found 246 selected birth defects in 12,008 live births in 1999, 148 among boys and 98 among girls. Congenital heart defects (particularly septal defects) were the most common (90.8/10,000), followed by defects of the genitourinary tract (34.1/10, 000) (particularly hypospadias in boys), digestive system (23.3/10,000) and central nervous system (14.9/10,000), orofacial clefts (10.8/10,000) and Down syndrome (8.3/10,000). Completeness was satisfactory: analysis of birth certificates resulted in the addition of two birth defect cases to the registry. Conclusion This is the first population-based analysis on selected major birth defects in the Region. The high birth prevalences for septal heart defect and hypospadias are probably due to the inclusion of minor defects and lack of coding standardization; the latter problem also seems important for other defects. However the data produced are useful for estimating the demands made on the health system by babies with birth defects.